Strategies used by people who inject drugs to avoid stigma in healthcare settings. (1st May 2019) - Biancarelli, Dea L.; Biello, Katie B.; Childs, Ellen; Drainoni, M.; Salhaney, Peter; Edeza, Alberto; Mimiaga, Matthew J; Saitz, Richard; Bazzi, Angela R.
Highlights: People who inject drugs frequently experience stigma in healthcare settings. People who inject drugs internalize, reject, and react to external stigma. When accessing care, people who inject drugs modify their behavior to avoid stigma. Community based organizations are preferred over large healthcare settings. Increased training and integrating healthcare into community settings is needed. Abstract: Background: People who inject drugs (PWID) have limited engagement in healthcare services and report frequent experiences of stigma and mistreatment when accessing services. This paper explores the impact of stigma against injection drug use on healthcare utilization among PWID in the U.S. Northeast. Methods: We recruited PWID through community-based organizations (CBOs; e.g., syringe service programs). Participants completed brief surveys and semi-structured interviews lasting approximately 45 min exploring HIV risk behaviors and prevention needs. Thematic analysis examined the emergent topic of stigma experiences in relation to healthcare utilization. Results: Among 33 PWID (55% male; age range 24–62 years; 67% White; 24% Latino), most used heroin (94%) and injected at least daily (60%). Experiences of dehumanization in healthcare settings were common, with many participants perceiving that they had been treated unfairly or discriminated against due to their injection drug use. As participants anticipated this type of stigma from healthcare providers, they developed strategies to avoid it, including delaying presenting for healthcare, not disclosing drug use, downplaying pain, and seeking care elsewhere. In contrast to large institutional healthcare settings, participants described non-stigmatizing environments within CBOs, where they experienced greater acceptance, mutual respect, and stronger connections with staff. Conclusions: Stigma against injection drug use carries important implications for PWID health. Increased provider training on addiction as a medical disorder could improve PWID healthcare experiences, and integrating health services into organizations frequented by PWID could increase utilization of health services by this population.